Management Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Pengelolaan Keuangan UMKM Kecamatan Tanggulangin - Assanniyah, Majalisi; Setyorini, Haryati (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
Micro, Small, and Medium Enterprises (MSMEs) have an important contribution in increasing Gross Domestic Product (GDP). Poor financial management not only has an impact on business growth but can have an impact on national economic growth. MSME players need knowledge and access to banking products and services. This study aims to examine the effect of financial literacy on MSME financial management in Tanggulangin District and to examine the effect of financial inclusion on MSME financial management in Tanggulangin District. This research is a quantitative research using data collection techniques, namely questionnaires. This study used a sample of 151 MSME actors. The data analysis technique in this study uses multiple linear regression analysis with a t test. The results of this study show that financial literacy has a significant positive effect on MSME financial management. Meanwhile, financial inclusion does not have a significant positive effect on the financial management of MSMEs in Tanggulangin District.